Apparent Nova in M31: M31N 2010-06d - Pietsch, W.; Henze, M.; Burwitz, V.; Liakos, A.; Hatzidimitriou, D.; Niarchos, P. (2010)
W. Pietsch, M. Henze, and V. Burwitz, Max-Planck-Institut fuer Extraterrestrische Physik; A. Liakos, Department of Physics, University of Athens; D. Hatzidimitriou, Department of Physics, University of Crete; and P. Niarchos, Department of Physics, University of Athens, report the detection of an apparent nova in M31 using observations with the UltraViolet/Optical Telescope (UVOT) onboard the Swift satellite. The object was serendipitously detected in the UVW1 filter (range 181-321 nm; UVOT observation number 31255018 with 4333-s exposure) starting on June 24.02 UT with a magnitude of 19.5 +/- 0.2. The position for the nova candidate, designated M31N 2010-06d, is R.A. = 0h42m55s.56, Decl. = +41d19'25".5 (equinox 2000.0; uncertainty 1".0), which is 127" east and 197" north of the core of M31. The source is clearly detected in the individual images. In the UVW1 filter, Swift observation number 31255014, starting on June 12.04 (4161-s exposure), and in the U filter, Swift observation number 31255017, starting on June 21.29 (1330-s exposure), no object was detected at the position of M31N 2010-06d, with limiting magnitudes of 20.5 and 19.7 (3 sigma), respectively. (All magnitudes are on the UVOT photometric system of Poole et al. 2008, MNRAS 383, 627, and have not been corrected for extinction.) M31N 2010-06d was confirmed on a stacked unfiltered CCD image composed of ten 60-s frames obtained at a 40-cm Cassegrain telescope with a focal reducer (f/5.1) equipped with a 2184x1472-pixel ST-10XME CCD camera (pixel size 6.8 microns square) at the Athens University Observatory on July 1.082 UT, yielding magnitude 17.8 (obtained from a photometric solution using R magnitudes of the Local Group Survey M31 catalogue of Massey et al. 2006) and position end figures 55s.62, 25".7 (uncertainty 0".5), fully consistent with the position of the Swift source. M31N 2010-06d is visible in the UV filter already several days before the detection in the optical (similar to novae M31N 2009-08a and M31N 2010-01b). Public data from the Swift data archive was used. Kamil Hornoch, Ondrejov Observatory, reports the independent discovery of M31N 2010-06d by Marek Wolf and himself on co-added 1620-s and co-added 1350-s R-band CCD frames taken by Hornoch on June 30.003 UT and by Wolf on July 1.022, respectively, with the 0.65-m telescope at Ondrejov. M31N 2010-06d is marginally visible on single images used for the co-added frames. Also, the new object is visible on pre-discovery co-added R-band frames taken with the same instrumentation during three previous nights, but is not present on numerous archive images taken at Ondrejov. M31N 2010-06d is located at R.A. = 0h42m55s.53, Decl. = +41o19'25".0 (equinox 2000.0), which is 126" east and 196" north of the center of M31. Available R-band magnitudes for M31N 2010-06d, measured by Hornoch: June 9.459 UT, [21.7 (P. Garnavich, C. Littlefield, N. Paul, and S. Bouzid, 1.83-m Vatican Advanced Technology Telescope); 18.152, [21.1 (P. Kubanek, J. Gorosabel, O. Lara-Gil, and M. Jelinek, 1.23-m telescope at Calar Alto); 27.034, 20.1 +/- 0.3 (K. Hornoch, 0.65-m telescope at Ondrejov); 28.014, 19.7 +/- 0.2 (Hornoch and P. Hornochova, 0.65-m telescope at Ondrejov); 28.040, 19.7 +/- 0.2 (Hornoch and Hornochova); 29.022, 19.2 +/- 0.2 (P. Zasche, 0.65-m telescope at Ondrejov); 29.034, 19.0 +/- 0.2 (Zasche); 30.003, 18.6 +/- 0.15 (Hornoch); 30.022, 18.65 +/- 0.1 (Hornoch); July 1.022, 18.3 +/- 0.1 (M. Wolf, 0.65-m telescope at Ondrejov).